Validity Of Business License Processing Through Online Single Submission Conducted By Notaries - Aldo Pratama; Budi Santoso (Journal Of Social Science (JoSS), 2024)
Economic slowdown after the COVID-19 pandemic had a big impact on Indonesia, economic recovery was achieved through OSS, which in practice many businessmen request to be processed through Notary. The article aims to analyze the authority of Notaries in processing Business Licenses in OSS. This article uses a normative juridical method. Based on UUJN and PP of Business Licensing, there’s no Notary's authority on licensing arrangements. The basis for the Notary's is only power of attorney from the businessman, where this power of attorney, based on Article 1320 of the Civil Code, is void because it violates existing regulations. There are no sanctions for Notaries, but businessmen are subject to administrative sanctions if they do not fulfill their commitments. Notaries should not accept requests for licensing and focus on education.